Epidemiological Study on Distribution Patterns of HIV Positive Cases and New AIDS Cases in Central Kalimantan Province - Wa Ode Azifa Malia; Wa Ode Fildayanti; Wa Ode Heldani; Yeti Purnama Alam; Yuliani; Zulfita (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: HIV/AIDS is a global public health problem that has a significant impact on the quality of life of individuals and creates a burden on the health care system. Central Kalimantan Province, with its unique geographic and demographic characteristics, faces its own challenges in controlling and combating the spread of HIV/AIDS. The dynamics of the spread of this disease in the region show a complexity that requires cross-sectoral attention and evidence-based interventions from stakeholders.Objective: This study aims to describe the distribution pattern of HIV/AIDS cases in Central Kalimantan Province during the period 2017 to 2021. The focus of the analysis includes the number of HIV and AIDS cases by gender and age group, using secondary data obtained from the Central Kalimantan Provincial Health Office.Method: The approach used in this study is a quantitative descriptive method. The data analyzed are secondary data sourced from official documents of the Central Kalimantan Provincial Health Office in the last five years. Data analysis is carried out by organizing information in the form of tables and graphs to facilitate the interpretation of case distribution patterns visually and statistically.Results: The analysis results show an increase in the number of HIV cases from 181 cases in 2017 to 264 cases in 2021, while AIDS cases increased from 48 cases to 143 cases in the same period. The majority of cases were found in the male group and the productive age group (25–49 years), reflecting the vulnerability of this group to HIV infection. In addition, in 2021, 22 deaths due to AIDS were recorded, most of which occurred in men. These findings indicate the importance of formulating prevention and treatment strategies that are more targeted at vulnerable groups, as well as the need to increase awareness and access to comprehensive health services.Conclusion: The increasing trend of HIV/AIDS cases in Central Kalimantan over the past five years shows the urgency of the need for serious attention from local governments and related sectors in implementing data-based, effective, and sustainable health policies. Interventions that focus on education, early detection, and expanding the scope of treatment and prevention services are expected to suppress the rate of spread of HIV/AIDS in this region.